Towards an understanding of marine fouling effects on the vortex-induced vibrations of circular cylinders: partial coverage issue. Issue 3 (16th March 2017) - Zeinoddini, M.; Bakhtiari, A.; Schoefs, F.; Zandi, A. P.
Abstract: The results of in-water vortex-induced vibration (VIV) experiments on circular cylinders artificially covered with barnacles are reported. The paper focusses on the effects of the partial coverage and the shape of the fouling elements. An artificial barnacle typical of marine fouling was synthesised using 3-D printing. Coverage ratios of 80, 50 and 30% were examined and the results compared with those from a smooth cylinder. The Reynolds number ranged from 5.8 × 10 3 to 6.6 × 10 4 . The experimental results show that the fouling reduced the peak VIV amplitude, narrowed the synchronisation region and lowered the hydrodynamic force coefficients such as the coefficients of lift force RMS, the mean drag force and the fluctuating drag force RMS. The shape of the artificial barnacles had little effect on the maximum oscillation amplitude. The coverage ratio appeared to have a lower impact on the lift force than those on the amplitude and the frequency responses.